The impact of post-merger integration on the customer-supplier relationship - Kato, Junichi; Schoenberg, Richard (Elsevier Science B.V., Amsterdam., 2014)
While the impact of mergers and acquisitions (M&A) on internal stakeholders has generated considerable empirical study, comparatively little academic attention has been paid as to how external stakeholders such as customers are affected by, and respond to, M&A activity. This study adopts case-study methodology to illuminate how the customer–supplier relationship is affected by post-merger integration processes in the business-to-business context, with the aim of increasing our understanding of why customers respond to M&A in the ways that they do. The findings highlight the importance of a set of critical customer relationship variables through which post-M&A integration actions can influence customers' perceptions of the merged organisation and, ultimately, their purchase decisions. We also identify a set of specific individual integration actions that appear to trigger changes in the critical customer relationship variables. Together, the findings contribute to our understanding of the precise mechanisms through which M&A can affect customers' purchase decisions and the combining firms' market-related performance. More broadly, consistent with the stakeholder perspective, they reinforce the need to take account of external as well as internal stakeholders when considering the drivers of M&A outcome. Implications are discussed for future research as well as for B2B service industry executives involved in M&A.